(untitled) (Indian Journal of Child Health, 2019)
Infantile spasm is one of the common seizure disorders with serious consequences. It is generally characterized by a muscle spasm of various intensity and distribution, salaam spells, and infantile myoclonic seizures with typical electroencephalography (EEG) features of hypsarrhythmia. Here, a unique case is being reported in which breath holding spells for few seconds were the sole presentation of infantile spasm. The EEG features of the case included typical high voltage spike and slow wave pattern followed by very poor suppression representing modified hypsarrhythmia, a classical feature of infantile spasm. Fast Fourier transformation of hypsarrhythmic spells confirmed the delta dominance with the highest power spectral density of delta waves. The breath holding spells being the sole presentation of infantile spasm makes it an important case clinically due to the possibility of misdiagnosis due to its inconspicuous presentation.